Institutional investors site visits, CSR performance, and large shareholder's expropriation - Jingwei Zhang (Cogent Business & Management, 2023)
The presence of institutional investors in a firm's ownership structure is often associated with improved corporate governance practices and increased focus on long-term sustainable value creation. This study investigates whether the presence of institutional investors and a strong CSR performance act as deterrents to large shareholder expropriation, which refers to the misuse of controlling power by large shareholders to extract personal benefits at the expense of minority shareholders. Empirical analysis yields several key findings. First, institutional investor site visits exhibit a significant negative association with large shareholder expropriation, implying that heightened institutional investor engagement through site visits is linked to improved corporate governance and a reduced propensity for opportunistic actions by large shareholders. Second, CSR plays a mediating role, elucidating that institutional investor engagement not only directly impacts governance but also indirectly shapes large shareholder behavior through CSR. Third, institutional ownership moderates the site visits-expropriation relationship, underscoring the significance of ownership structure in governance dynamics. This study contributes to the existing literature by offering empirical evidence of how institutional investor engagement, mediated by CSR, can curtail large shareholder expropriation. These findings expand comprehension of the mechanisms through which institutional investors bolster governance and emphasize the need to consider ownership structure when analyzing governance dynamics. The implications of this study are multifaceted. Firms can enhance corporate governance by fostering engagement with institutional investors, leading to improved CSR practices and reduced risks of large shareholder expropriation. Policymakers should recognize the importance of institutional ownership and investor involvement when crafting governance regulations, as these elements strengthen governance mechanisms.
Keywords: 650; corporate governance; corporate social responsibility; expropriation; institutional investors; large shareholder